Peer Tutoring to Improve the Speaking Proficiency of Multiage EFL Students - Dimiar Ariesinta; Agus Widyantoro (IJEE (INDONESIAN JOURNAL OF ENGLISH EDUCATION), 2024)
Previously, educators created a multiage classroom to address the growing age gap within a class and the unresolved issue of teacher shortage. However, some schools in specific countries currently use this system, which provides significant benefits and positive developments to their fall-behind students or classes. This study conducted peer tutoring to address speaking issues in the classroom and bridge the gap in students' basic English knowledge. Besides, it is eager to improve students' speaking skills in a multiage EFL classroom and enrich literature in non-formal education. This study used McNiff and Whitehead's (2006) theory cycle for classroom action research: observation, reflection, action, evaluation, and modification. Data were collected through tests and interviews, and then the questionnaire was added and analysed using the NVivo 12 Pro application. The finding revealed that peer tutoring improved the multiage students' speaking proficiency in their fluency, vocabulary, and comprehension. In a non-academic setting, peer tutoring effectively boosted the students' self-confidence and collaboration and demonstrated grade-level skills or accelerated learning in the class.